2021
DOI: 10.1021/acsami.1c11468
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral Framework Nucleic Acids Ameliorate Insulin Resistance in Type 2 Diabetes Mellitus via the PI3K/Akt Pathway

Abstract: Insulin resistance (IR) is one of the essential conditions in the development of type 2 diabetes mellitus (T2DM). IR occurs in hepatic cells when the insulin receptor substrate-1 (IRS-1)/phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway is downregulated; thus, activating this pathway can significantly improve insulin sensitivity and ameliorate T2DM. Tetrahedral framework nucleic acids (tFNAs), a DNA nanomaterial, are synthesized from four single-stranded DNA molecules. tFNAs possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…DNA nanomaterials with distinctive spatial configurations are known as tetrahedral framework nucleic acids (TFNAs) (69). TFNAs have excellent biosafety with anti-inflammatory, antioxidant, anti-fibrotic, angiogenic, and skin wound healing activities with little toxicity (70).…”
Section: Role Of Pyroptosis and Inflammasomes In Wound Healingmentioning
confidence: 99%
“…DNA nanomaterials with distinctive spatial configurations are known as tetrahedral framework nucleic acids (TFNAs) (69). TFNAs have excellent biosafety with anti-inflammatory, antioxidant, anti-fibrotic, angiogenic, and skin wound healing activities with little toxicity (70).…”
Section: Role Of Pyroptosis and Inflammasomes In Wound Healingmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a disease caused by lack of insulin secretion or insulin resistance, which cause the body to experience persistent hyperglycemia and long-term metabolic disorders. DM is classified into type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM), in which T2DM accounts for nearly 95% of individuals, and the number of patients is increasing year by year [1,2]. Insulin resistance (IR) is one of the essential conditions in the development of type 2 diabetes mellitus, and insulin reduces blood sugar levels and improves IR by promoting glucose absorption [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers have found that suppression of the PI3K/Akt signaling pathway is implicated in high-glucose-induced cell dysfunction [ 33 ]. As shown in Figure 1 , insulin activates and binds to the insulin receptor (InsR), inducing PI3K-AKT activation.…”
Section: Discussionmentioning
confidence: 99%